Creation of Dominant Elements in Light Architecture in the Organization of Urban Planning and Landscape Architecture in Uzbekistan (On the Example of Samarkand) (Czech Journal of Multidisciplinary Innovations, 2022)
The spectacular lighting of landmarks in many cities around the world, in which lighting engineers had previously played a major role and architects as officials who agreed on proposed solutions, has always attracted public interest in new improvement opportunities and new environmental standards shaped by lighting. These opportunities are steadily increasing due to advances in lighting and the improvement of living standards. For the profession of architect, according to the author, an objective and urgent need to master the art of lighting has matured not as an exotic, insignificant, engineering task, but as one of the multifaceted and promising "architectural" problems that must be solved in the process of designing the city and most of the objects in it along with and in combination with the traditional tasks of creating an urban, architectural and design form. With this formulation of the case, philosophy is enriched and the field of professional activity expands: architecture should be created not only for life in it and its perception during the day (this is one visual state of the surrounding world, but also at night, and at the same time look not like a simple repetition of the daytime (which is impossible in the exterior), but have its own characteristic figurative and emotional qualities. This should be considered the second visual state and architectural image of the urban environment.